Effect of Slow and Fast Pranayama Training on Handgrip Strength and Endurance in Healthy Volunteers - Thangavel, Dinesh (JCDR Research and Publications (P) Limited, 2014)
Background: Pranayama has been assigned very important role in yogic system of exercises and is said to be much more important than yogasanas for keeping sound health. Also different pranayamas produce divergent physiological effects. Aim: To study the effect of 12 weeks training of slow and fast pranayama on handgrip strength and endurance in young, healthy volunteers of JIPMER population. Settings and Design: Present study was conducted in the Department of Physiology, JIPMER in 2011-12 (1.06.11 to 1.04.12). Materials and Methods: Total of 91 volunteer subjects were randomised into slow pranayama (SPG) (n=29), fast pranayama (FPG) (n=32) and control groups (CG) (n=30). Supervised pranayama training (SPG - Nadisodhana, Pranav pranayama and Savitri pranayama; FPG - Kapalabhati, Bhastrika and Kukkuriya pranayama) was given for 30 minutes thrice a week for 12 weeks to both slow and fast pranayama groups by certified yoga trainer. Hand grip strength (HGS) and endurance (HGE) parameters were recorded using handgrip dynamometer (Rolex, India) at baseline and after 12 weeks of pranayama training. Statistical Analysis Used: Longitudinal changes in each group were compared by using Student’s paired t-test. Delta changes in each group were analysed by ANOVA with Tukey post-hoc analysis. Results: In SPG significant improvement occurred only in HGE parameter from 83.95±45.06 to 101.62±53.87 (seconds) (p<0.001) whereas in FPG, significant improvement was observed in HGS from 33.31±9.83 to 37.9±9.41 (Kilograms) (p=0.01) as well as in HGE from 92.78±41.37 to 116.56±58.54 (seconds) (p=0.004). Using Students unpaired t-test difference between the groups in HGS is found to be 1.17±5.485 in SPG and in FPG is 4.59±7.26 (p=0.39); HGE difference in SPG is 1.77±21.17 and in FPG is 2.38±43.27 (p>0.05). Conclusion: Pranayama training decreases sympathetic activity, resulting in mental relaxation and decreased autonomic arousal thereby, decreasing force fluctuations during isometric contraction. This is reflected as improvement in HGS and HGE.